Evaluation of chemical events at Army chemical agent disposal facilities (The National Academies Press, 2002)
"The National Research Council was asked by the Army to form a special, ad hoc committee to investigate whether incidents involving chemical warfare material stored, processed, and destroyed at the two operational Army chemical demilitarization sites provide useful information for the safe operation of future sites"--P. 1.